Reflections on Williamson on Logic and Validity. - Priest, Graham (Problems / Problemos)
The article "Reflections on Williamson on Logic and Validity" by Graham Priest discusses debates with Tim Williamson on fundamental issues concerning logic. Williamson argues that logic is not solely about validity but also reveals fundamental truths about the world. The article delves into the nature of logic, abductive methodology, and the strength of classical logic compared to non-classical logics. It also explores contra-classical logics like Aristotelian Syllogistic and überconsistent logics. The conclusion highlights areas of agreement and disagreement between the authors, aiming to advance discussions on these complex topics.